2023
DOI: 10.3390/cancers15041207
|View full text |Cite
|
Sign up to set email alerts
|

How Much Stress Does a Surgeon Endure? The Effects of the Robotic Approach on the Autonomic Nervous System of a Surgeon in the Modern Era of Thoracic Surgery

Abstract: (1) Objective: the purpose of this study was to evaluate and quantify the stress to which a surgeon is subjected during his/her surgical activity; we compared the individual clinical and psychological responses to stress of two surgeons during their surgical activities via robotic and open approaches. (2) Materials and methods: This was a prospective observational study in which we progressively collected data concerning the surgical performances of two different thoracic surgeons (October 2021–June 2022). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Future studies could consider the applications of long‐duration measurements which may lend data on long‐term effects and recovery 57 . In the OT setting, HR analysis was the only feasible physiological measure of cardiovascular reactivity, however in a simulated setting, additional physiological measures could include galvanic skin conductance, blood pressure, respiratory activity, and plasma cortisol 59–61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies could consider the applications of long‐duration measurements which may lend data on long‐term effects and recovery 57 . In the OT setting, HR analysis was the only feasible physiological measure of cardiovascular reactivity, however in a simulated setting, additional physiological measures could include galvanic skin conductance, blood pressure, respiratory activity, and plasma cortisol 59–61 …”
Section: Discussionmentioning
confidence: 99%
“…57 In the OT setting, HR analysis was the only feasible physiological measure of cardiovascular reactivity, however in a simulated setting, additional physiological measures could include galvanic skin conductance, blood pressure, respiratory activity, and plasma cortisol. [59][60][61] The SURG-TLX has been gaining popularity recently in providing rapid and easily repeatable assessment of cognitive load of surgeons and teams in the operating environment. [62][63][64] In the future, it may prove a useful tool in understanding the effect that physical fatigue, time pressure, distraction, evaluation apprehension, and environmental factors (e.g., noise, heat, music) may have on a surgeon.…”
Section: The Instruments Of Stress Measurementmentioning
confidence: 99%
“…Mazella et al found that robot-assisted lung resection had decreased autonomic responses in comparison to open approaches, supporting the idea that robotic surgery may be less stressful for surgeons. [20] Given the equipment necessary to examine physical demand, such as EMG, we chose to use saliva to measure physiological stress in the operating room. Salivary amylase has been utilized in other elds to measure physiologic stress as a proxy for autonomic nervous system response but has not been used to measure stress during surgical cases.…”
Section: Discussionmentioning
confidence: 99%